Resourcefulness, narratives, and identity in science, technology, engineering, arts and mathematics education: A perspective of makerspaces for rural communities in Colombia - Avendano-Uribe, Bryann E.; Ojeda-Ramírez, Santiago; Perez-Baron, Jonathan (Frontiers in Education, 2022)
Disparities of scientific education (STEM) in rural and remote communities are exacerbating inequalities and taking away opportunities for youth to explore their scientific interests and participate in science-making globally. Maker education in rural and remote areas of Latin America could boost the participation of rural communities in scientific education and open alternatives to the lack of higher literacy rates and STEM education. In Colombia, tertiary education has been making efforts to close this gap through the Itinerant Technical Academies of Servicio Nacional de Aprendizaje (SENA: National Learning Service). Participants in the Technical Academies create relevant technologies for their context, reflecting on their cultural values and aesthetics. In this contribution, we describe three projects conducted in the itinerant Technical Academies of rural Colombia in Narino to exemplify how participants made their artefacts relevant to their culture using available resources, materials, and practices. Students are using available resources to create artefacts that are relevant to their social contexts and aligned with constructivist practices. We propose and discuss three characteristics that have emerged in makerspaces situated in rural Colombia: i. Narratives, ii. Resourcefulness, and iii. Identities and we suggest that makers, scholars, policymakers, and educators should pay attention to those three elements to guide future studies and further research on maker education in the Global South.